Answer:14
Step-by-step explanation:
Its slope is -3 so we got
y=-3x+b
and the graph passes through (1,1)
so we got b=4
the equation is y=-3x+4
Hope this will help
Sum means add
(x+5) + (-4x-2) + (2x-1)
=-3x+3+(2x-1)
=-x+2
Factor out the cos<span>θ:
</span>cosθ (2sin<span>θ + sqrt3) = 0
</span>Therefore, the only ways this can happen are if either cosθ = 0 or if (2sin<span>θ + sqrt3) = 0
</span>The first case, cosθ = 0 only at θ <span>= pi/2, 3pi/2.
</span>The second case, <span>(2sin<span>θ + sqrt3) = 0 simplifies to:
</span></span>sin<span>θ = (-sqrt3)/2
</span><span><span>θ = 4pi/3, 5pi/3
</span></span><span><span>Therefore the answer is A.
</span></span>